1986
DOI: 10.1073/pnas.83.3.740
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a genetic difference confined to mutation of H-2K on the incidence of pregnancy block in mice.

Abstract: In mice, pregnancy is often terminated when the stud male is removed and the pregnant female is exposed to the presence or scent of an unfamiliar male. It is reported here that the incidence of such blocking of pregnancy was higher when the stud and unfamiliar male differed by mutation of the H-2K class I gene of the major histocompatibility complex than when the stud and unfamiliar males were genetically identical. Thus, the olfactory distinction of mice differing by mutation of the H-2K gene, previously demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…They act through a complex mixture of volatile and nonvolatile metabolites bound and released by urinary proteins or peptides [52][53][54]. Volatiles from urine also vary according to social status, diet, and animals' bacterial gut flora [11,48,65], while MUPs and MHC peptides are hard-wired into the genome and stable throughout the life of the animal [31,53,64].…”
Section: Discussionmentioning
confidence: 99%
“…They act through a complex mixture of volatile and nonvolatile metabolites bound and released by urinary proteins or peptides [52][53][54]. Volatiles from urine also vary according to social status, diet, and animals' bacterial gut flora [11,48,65], while MUPs and MHC peptides are hard-wired into the genome and stable throughout the life of the animal [31,53,64].…”
Section: Discussionmentioning
confidence: 99%
“…This effect can be seen when the only differences between the stud and strange males are in the alleles of the MHC (Yamazaki et al, 1983b). Indeed, it was shown that abortion could be elicited when the only genetic differences between the stud and the foreign male were three point mutations in the H-2K b molecule (H-2K b for the stud versus H-2K bm1 for the strange male and vice versa; Yamazaki et al, 1986b). Abortion can be prevented by administration of prolactin or progesterone (Dominic, 1966a), indicating that the effect is likely to be due to neuroendorine disturbance.…”
Section: Mhc-associated Odours and Reproductionmentioning
confidence: 99%
“…There is evidence that the MHC plays a role in odor-mediated pregnancy block (Bruce effect): female mice are more likely to block pregnancy if the stud male and the introduced male are MHC dissimilar than when they are genetically identical (Yamazaki et al 1986). However, no one has tested whether MHC-similar males are more likely to trigger pregnancy block than males who are MHC dissimilar to females.…”
Section: Abortional Selection: Cryptic Female Choice?mentioning
confidence: 99%